Value chain and government support in generating innovation in the creative industry in Yogyakarta - Zidni Husnia Fachrunnisa; Rahandhika Ivan Adyaksana; Siti Afidatul Khotijah (Department of Accounting Universitas PGRI Yogyakarta, 2026)
Today, the innovation process is decentralized across a company's value chain and involves various actors. This study focuses on how the value chain enhances innovation and the government's impact on innovation in the creative industry in Yogyakarta. The research method used was qualitative research with data collection through interviews. The population in this study was the creative industry in the Special Region of Yogyakarta, with 13 creative industry actors from various business sectors serving as samples. The results show that each stage of the value chain—creation, production, distribution, and commercialization—can generate innovation for the creative industry, and government support at each stage of the value chain can encourage the creative industry to innovate. As a result, innovation in the creative industry can be increased by optimizing activities at each value chain and with government support. Suggestions for future research include expanding the sample, particularly to sectors not yet examined in this study, to obtain more comprehensive results.